Evaluación Genética de la Piara de la Escuela Agrícola Panamericana Zamorano utilizando el software VIRTUALBLUP® - Flores R., Mariela S.; Orellana Q., Carlos L. (Zamorano: Escuela Agrícola Panamericana, 2025)
Zootecnia